The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00737-018-0874-6
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: PTSD and gender: could gender differences in war trauma types, symptom clusters and risk factors predict gender differences in PTSD prevalence?

Abstract: The female-male ratio in the prevalence of post-traumatic stress disorder (PTSD) is approximately 2:1. Gender differences in experienced trauma types, PTSD symptom clusters, and PTSD risk factors are unclear. We aimed to address this gap using a cross-sectional design. A sample of 991 civilians (522 women, 469 men) from South Lebanon was randomly selected in 2007, after the 2006 war. Trauma types were grouped into disaster and accident, loss, chronic disease, non-malignant disease, and violence. PTSD symptom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Next to trauma load and stigmatization, gender was an important factor influencing PTSD symptom severity, with women indicating higher symptom scores than men. Furthermore, we found that the higher symptoms of women persisted throughout therapy, at the end of which women still presented with higher symptoms than men ( 55 57 ).…”
Section: Discussionmentioning
confidence: 71%
“…Next to trauma load and stigmatization, gender was an important factor influencing PTSD symptom severity, with women indicating higher symptom scores than men. Furthermore, we found that the higher symptoms of women persisted throughout therapy, at the end of which women still presented with higher symptoms than men ( 55 57 ).…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, this study indicates an interesting reversal in the gender distribution of mental disorders. As noted by most trauma studies, women have higher incidence rates of mental health problems like PTSS and depression than their male counterparts (44,45), explained partially by physiological differences or distinguished psychological mechanism (46). On the contrary, the evidence from this study supports that males are more possibly diagnosed with psychological disorders under the pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
“…traumatic exposure, genetic and biological vulnerability). Males and females with PTSD were also found to differ in terms of symptom cluster manifestation (Farhood et al, 2018; Yehuda et al, 2015). ASD, on the other hand, is more common in males than in females, with a male to female ratio varying from 3:1 (Loomes et al, 2017) to 16:1 (Ferri et al, 2018).…”
Section: Introductionmentioning
confidence: 98%